The Family Assistance and Determinants of Stunting: An Operational Study in Donggala Regency - Fahmi Hafid; Taufiqurrahman Taufiqurrahman; Nasrul Nasrul; Sarina Sariman; Syahriar; Ilham (Politeknik Kesehatan Kemenkes Surabaya, 2025)
Stunting remains a significant public health issue in Donggala Regency, impacting long-term human resource quality. This study analyzed stunting determinants through a family-based approach using a cross-sectional survey on November 13–18, 2024, involving 908 families at risk of stunting. Data were collected through questionnaires, body length measurements using Length Board Measuring (LMB), and age verification from birth certificates or KIA books. Statistical analysis employed Chi-Square, Logistic Regression, and T-Test with STATA software, while the WHO-Antro 2005 software calculated Z-Score TB/U values. Most respondents were housewives (90.7%), educated >9 years (80.1%), aged ≥20 years (94.4%), and lived in rural areas (93.6%). Families receiving assistance showed a lower stunting prevalence (22.7%) compared to controls (30%). Proper sanitation and clean water access reduced stunting prevalence to 24.1%, versus 63.6% in families lacking access. Boys aged 12–23 months were the most vulnerable group. Family assistance improved knowledge of balanced diets and hygiene, reducing stunting prevalence. Expanding family assistance programs, enhancing sanitation infrastructure, and increasing access to clean water are crucial. Strengthening posyandu to provide targeted nutritional interventions, especially for children aged 12–23 months, is recommended to combat stunting effectively in Donggala Regency.